Socio-technical Aspects of Smallholder Beekeeping Adoption of Apis cerana in Wanagama Teaching Forest, Gunungkidul, Yogyakarta - Dwiko Budi Permadi; Nafiatul Umami; Ananto Triyogo; Rini Pujiarti; Bekti Larasati; Ratih Madya Septiana (Buletin Peternakan, 2021)
The successful rehabilitation of Wanagama teaching forests, which began in the late of 1960s, has created a distinctive forest ecosystem. Currently the forests become the habitat of Apis cerana, enterprised by the surrounding villagers to produce natural forest honey as a non-timber forest product. This paper aims to explore the adoption of smallholder beekeeping of A. cerana, the beekeepers’ socio-economic characteristics, the potential and value of forest honey production, the distribution of bee-boxes inside the forests and potential tree sources of nectar and pollen. Data collection was carried out in July - September 2019 with in-depth interview techniques to 38 beekeepers. Field observations and ground checks were carried out on the sites where beekeepers were placing the bee-boxes in the forest. In addition, an analysis of aerial photograph images taken with drone was also carried out to identify the area of trees as sources of nectar and pollen. The results show that between 1982 and 2019 the development of the adoption of the A. cerana beekeeping increased significantly. The total production of honey from 506 bee-boxes reached 658 liters or 894.9 kg in year of 2018/2019. The number of bee-boxes placed in Wanagama was mainly distributed inside Compartment of 13, 17, 14, 16, 5, and 18. Acacia mangium, eucalyptus, cajuput and mahogany were the main types of nectar-producing trees, in addition to the abundance of flowering undergrowth plants. Many of the challenges faced by honey beekeepers included climate change, the shortage of nectar and pollen sources, pests and diseases and human disturbances. This research suggests the need for a social, institutional and technical approaches to increase the forest productivity as sources of nectar and pollen. It is suggested encouraging the smallholders to adopt beekeeping as the main livelihood alternatives in future and planting more trees in Wanagama forests.